Analysis of the Impact of using Digital Storytelling-based Interactive Learning Media on IPAS Comprehension - Dhiva Nawalsani Al Fadhila; Ratnasari Diah Utami (Universitas Muhammadiyah Surakarta, 2025)
Purpose: Driven by the low utilization of digital learning media, this study aims to examine the impact of Digital Storytelling-based interactive learning media on students' understanding of IPAS concepts.Methodology: A quantitative pretest-posttest control group design was used with fifth-grade students at SD Muhammadiyah Program Unggulan Colomadu. Class VA served as the control group and class VB as the experimental group. Data were collected through validated and reliable multiple-choice tests and analyzed using the Shapiro-Wilk test, Levene's test, independent t-test, and paired t-test.Results: Findings show that the data were normally distributed and homogeneous. The experimental class demonstrated a significant improvement from pretest to postest, while the control class showed only minimal gain. The independent t-test confirmed significant differences between posttest scores of both groups.Applications/Originality/Value: The study provides evidence that Digital Storytelling is an effective technology-based learning medium for improving IPAS comprehension and offers a relevant alternative for teachers in designing engaging and interactive digital learning experiences for elementary students.